2019
DOI: 10.3389/fbioe.2019.00283
|View full text |Cite
|
Sign up to set email alerts
|

The Biotic and Abiotic Carbon Monoxide Formation During Aerobic Co-digestion of Dairy Cattle Manure With Green Waste and Sawdust

Abstract: Carbon monoxide (CO), an air pollutant and a toxic gas to humans, can be generated during aerobic digestion of organic waste. CO is produced due to thermochemical processes, and also produced or consumed by cohorts of methanogenic, acetogenic, or sulfate-reducing bacteria. The exact mechanisms of biotic and abiotic formation of CO in aerobic digestion (particularly the effects of process temperature) are still not known. This study aimed to determine the temporal variation in CO concentrations during the aerob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 40 publications
8
36
2
Order By: Relevance
“…CO is formed as a result of the biological decomposition of the OF together with other gases such as CO 2 , CH 4 , H 2 , nitrogen compounds, volatile organic compounds (VOCs), and H 2 S [15]. CO formation has been observed during composting of green waste [16], green waste with manure [17], organic waste [18,19], and municipal waste [20,21]. The discovery of CO formation during composting was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…CO is formed as a result of the biological decomposition of the OF together with other gases such as CO 2 , CH 4 , H 2 , nitrogen compounds, volatile organic compounds (VOCs), and H 2 S [15]. CO formation has been observed during composting of green waste [16], green waste with manure [17], organic waste [18,19], and municipal waste [20,21]. The discovery of CO formation during composting was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetics data for CO production rates during composting of organic waste were also reported elsewhere [29]. [27], ** estimated using raw data in [29]. [27], ** estimated using raw data in [29].…”
Section: Methodsmentioning
confidence: 99%
“…Production of CO is a result of the biological decomposition of organic matter, which also generates CO 2 , CH 4 , H 2 , nitrogen compounds, VOC, and H 2 S [3]. CO emissions have been observed during the composting of green waste [4], green waste with manure [5], organic waste [2], and aerobic biostabilization of the municipal waste [6]. The detection of CO during the pioneering experiments was a surprise due to the widespread belief in its primary production by incomplete combustion [7].…”
Section: Introductionmentioning
confidence: 99%
“…In recent work [4], we have indicated that CO production during biowaste aerobic digestion can be biotic and abiotic in nature. The main observation was that CO concentrations varied throughout the process, with the temperature being the main influencing factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation